Shakespeare as Literary Dramatist - Erne, Lukas 1968- (Cambridge University Press, 2013)
Now in a new edition, Lukas Erne's groundbreaking study argues that Shakespeare, apart from being a playwright who wrote theatrical texts for the stage, was also a literary dramatist who produced reading texts for the page. Examining the evidence from early published playbooks, Erne argues that Shakespeare wrote many of his plays with a readership in mind and that these 'literary' texts would have been abridged for the stage because they were too long for performance. The variant early texts of Romeo and Juliet, Henry V and Hamlet are shown to reveal important insights into the different media for which Shakespeare designed his plays. This revised and updated edition includes a new and substantial preface that reviews and intervenes in the controversy the study has triggered and lists reviews, articles and books which respond to or build on the first edition